Fatigue damage mechanisms of bridging fibers in titanium metal matrix composites - Tamin, M. N.; Ghonem, H. (ASME, 2000)
This paper investigates the fatigue damage mechanisms of SiC fibers bridging a fatigue crack in unidirectional reinforced titanium matrix composites. For this purpose, an experimental/computational fiber fracture model is developed on the basis of the occurrence of two damage events taking place along a bridging fiber. These events are the time-dependent evolution of axial stresses and the simultaneous strength degradation of the fiber due to cyclic-related damage processes. The stress evolution in a fiber is calculated using the finite element method employing a cylinder model of a fiber embedded in a cracked matrix phase. The model considers the visco-plastic behavior of the matrix phase at elevated temperature loadings. The failure strength of the as-received SiC fiber are determined through a series of monotonic tension, residual fatigue strength and fatigue-life tests performed on SiC fibers at different temperatures. In order to take into account the notch-like effects resulting from the presence of fiber coating cracks and possible deflection of fiber/matrix interfacial cracks, the fatigue strength of the as-received SiC fiber was modified using elastic stress localization. The resulting fatigue strength of bridging fibers was found to be about 56 percent less than the corresponding strength of as-received fibers. The fiber stress evolution curve and the modified fatigue strength curve were then combined to predict the life of bridging fibers. Results of the model are compared with those obtained experimentally for bridging fibers in SiC/Timetal-21S composite subjected to load conditions including low and high loading frequency at 500 and 650 Â°C.